Generalized harmonic number summation formulae via hypergeometric series and digamma functions - Liu, Hongmei; Zhou, Wenshu; Ding, Shuyan (Journal of difference equations and applications, 2017)
By computing the derivatives of five classical hypergeometric summation theorems, and applying the related properties of the digamma function, we derive a large number of closed summation formulae for generalized harmonic numbers.